KINERJA EKONOMI DAN DAMPAKNYA TERHADAP DEGRADASI LINGKUNGAN HIDUP DI INDONESIA - Muhammad Arif; Zana Zein Hardimanto (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2023)
This research was conducted with the main objective of examining the impact of the growth of the main economic sectors on environmental degradation in Indonesia. In achieving this goal, this research was carried out based on panel data procedures for all provinces in Indonesia for 5 years’ period using environmental quality Index and forest land conversion as a representation of environmental damage and Regional Domestic Product for agricultural sector, mining and manufacture, as indicators of the development of the main economic sectors in Indonesia. The results found that the Fixed Effect Model is the most appropriate method to explain the relationship between variables in this study, the results of the analysis in this study also confirm that forest land conversion is a strong determinant of environmental damage in Indonesia, on the others side the development of Regional Domestic Product values for the agricultural sector is statistically known to be able to improve the quality of the environment in Indonesia, while the development of the value of the Regional Domestic Product for Mining and Industry although it has a negative value, statistically has not been able to affect the quality of the environment in Indonesia.